THE EFFECT OF FREELETIC SPORT TO VO2 MAX LEVELS ON THE FREELETIC COMMUNITY MEMBERS IN MAKASSAR CITY - Irianto Irianto; Hasnah Hasnah (Nusantara Medical Science Journal, 2018)
Introduction: VO2 max is the maximum oxygen amount of  that can be consumed during intense physical activity until eventually fatigue occurs. A person with a good  level of VO2 max means having good physical fitness as well. Physical fitness gives the ability to a person to do daily productive work in the absence of excessive fatigue. The low one cardiorespiratory fitness may incrase the risk of death from heart disease and hypertension. Giving freeletic exercise is one of the techniques used to improve cardiorespiratory fitness or VO2 max. Methods: This research is Pre-experimental research with one group pre-post test design. The sample of the study amounted to 20 people and freeletic exercise was given 12 times. The measuring tool used is Multistage Test of Fitness / Beep Test to know the level VO2 max  of sample  before and after freeletic sporting practice. Results: The results of this study indicate that 17 respondents experienced a significant increase in VO2 max and 3 other respondents did not experience improvement by giving 12 times freeletic sports exercise. Conclusion: Based on Paired T test to know whether or not there is influence, it can be concluded that there is influence of giving freeletic sport to max VO2 level on freeletic community member after given 12 times (p< 0,001, p<0,05) freeletic sport practice.